PROFIT ANALYSIS OF PIG FARMING BUSINESS IN LANSOT VILLAGE, SOUTH TOMOHON DISTRICT (Case Study) - Franky N.S Oroh; Ingriet D.R Lumenta (Animal Husbandry Department, Faculty of Agriculture Gorontalo State University, 2026)
This research aims to evaluate the financial viability of Deglothy Farm, a pig farming enteIDRrise located in Lansot Village, South Tomohon District. The study utilized surveys and interviews, drawing on both primary and secondary data sources. The analysis focused on calculating revenues and expenses over a one-year period, from April 2024 to March 2025. Findings indicate that Deglothy Farm operates with a high level of efficiency. The total annual operational expenses amounted to IDR 557,993,952, comprising fixed costs of IDR 56,811,952 and variable costs of IDR 501,182,000. During the same period, the farm generated total revenue of IDR 1,344,250,000, resulting in a net annual profit of IDR 786,256,048. In summary, Deglothy Farm’s pig farming business proves to be economically profitable and sustainable.